2018
DOI: 10.3389/fimmu.2018.01215
|View full text |Cite|
|
Sign up to set email alerts
|

Fake News or Weak Science? Visibility and Characterization of Antivaccine Webpages Returned by Google in Different Languages and Countries

Abstract: The 1998 Lancet paper by Wakefield et al., despite subsequent retraction and evidence indicating no causal link between vaccinations and autism, triggered significant parental concern. The aim of this study was to analyze the online information available on this topic. Using localized versions of Google, we searched “autism vaccine” in English, French, Italian, Portuguese, Mandarin, and Arabic and analyzed 200 websites for each search engine result page (SERP). A common feature was the newsworthiness of the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 36 publications
(38 reference statements)
4
69
0
3
Order By: Relevance
“…This was also used when comparing the frequency of HONcode-certified webpages in the top 10 results vs. the remaining 140 websites. The statistical analysis was pre-defined and followed exactly the same design used in our previous studies (7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was also used when comparing the frequency of HONcode-certified webpages in the top 10 results vs. the remaining 140 websites. The statistical analysis was pre-defined and followed exactly the same design used in our previous studies (7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore important to assess the trustworthiness of the probiotics information that can be found online. For this purpose, we took advantage of an established methodology previously used to analyze health information quality on antioxidants and vaccines (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Records of AEFI in individuals vaccinated in the Brazilian public system are made available by the Ministry of Health, through the General Coordination of the PNI (CGPNI, in Portuguese), in the Information System on Surveillance of Adverse Events Following Immunization (SI-EAPV, in Portuguese) 8,9 . The PNI launched the surveillance of AEFI in 1992, and compulsory notification was established on July 15, 2005 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Another study evaluating JAMA points reported that the google.com and google.co.uk websites had higher points compared with the localized interfaces in English-Australia, French, and Italian. [21] According to our results, the reliability of anti-vaccination articles on websites and news sites related to this topic in Turkey seems to belower.…”
Section: Discussionmentioning
confidence: 64%